Traditional Impacities in The Frame of Worship: A Study of Fidyah Semyang Ritual in Suka Datang Village, North Curup Sub-District - Laras Shesa; Isnaini isnaini; Agus Riyan Oktori (AJIS: Academic Journal of Islamic Studies, 2022)
The tradition of paying fidyah with gold for people who have passed away in Suka Datang Village, Curup Utara District, Rejang Lebong Regency, or what the people there call Fidyah Semyang, is the subject of discussion for this study. The purpose of this study is to deeply examine the implementation and mechanisms of the performance of the payment of fidyah and to investigate the views of Islamic law on the practice of fidyah that applies in society. This research is a type of Field Research with a qualitative approach using phenomenology, ethnography, and a case study. The data sources in the study are divided into two types: field data as primary and library data as secondary data sources. From the implementation of the tradition of Fidyah Semyang, there was some equipment to carry out ritual activities in the form of gold, money, and fragrance. Therefore, from the side of Islamic law, the practice is obligatory if there is a will from the deceased, but if the dead does not make a will, then the law is sunnah. If it is viewed from the theory of ‘Urf, the tradition of Fidyah semyang is included in the realm of Al-‘urf Al-Fasid (broken rule). Then, if it is viewed from the practical point of view, the recipients of fidyah should also be poor and needy to be replaced by religious scholars who can be said to be adequate